Dadibi, Tok Pisin, English : Po Dage Dabe - Whitby, Clyde (Negabo, Simbu Province, Papua New Guinea : [Summer Institute of Linguistics], 1994)
The first section of this book lists words alphabetically in Dadibi. The second is arranged by topic for ease of non-native speakers. The third section describes basic grammar concepts.
Includes index.
In Dadibi, Tok Pisin and English
Keywords: Daribi language -- Dictionaries -- Polyglot; Daribi language -- Dictionaries -- Tok Pisin; Daribi language -- Dictionaries -- English